1. ## Evaluating a function

I have been trying this for 2 days and I can"t seem to get the right answer \

when f(x) =(x+1)
and f(x) = (-x)
when its (x-1) i get the following
2(x-1)^2 +7(x-1)-8
2x^2-4x+2+7x+7x-8
2x^2+3x-1 Is my solution right?

And -X i am just not sure I got 2x^2-8x-8 this as my answer

2. ## Re: Evaluating a function

I get:
$f(x-1) = 2(x-1)^2+7(x-1)-8 = 2(x^2-2x+1)+7x-7-8 = 2x^2-4x+2+7x-15 = 2x^2+3x-13$
$f(-x)=2(-x)^2+7(-x)-8=2x^2-7x-8$

3. ## Re: Evaluating a function

Originally Posted by M670
I have been trying this for 2 days and I can"t seem to get the right answer \

when f(x) =(x+1)
and f(x) = (-x)
when its (x-1) i get the following
2(x-1)^2 +7(x-1)-8
2x^2-4x+2+7x+7x-8
2x^2+3x-1 Is my solution right?And -X i am just not sure I got 2x^2-8x-8 this as my answer
I don't understand what you are to do.

If $f(x)=2x^2+7x-8$ then
$f(x+1)=2(x+1)^2+7(x+1)-8=2x^2+4x+2+7x+7-8=2x^2+11x+1$.

4. ## Re: Evaluating a function

Sorry i Corrected my formula it was (x+1) not (x-1) I believe it changes the answer to mine

5. ## Re: Evaluating a function

Originally Posted by Plato
I don't understand what you are to do.

If $f(x)=2x^2+7x-8$ then
$f(x+1)=2(x+1)^2+7(x+1)-8-=2x^2+4x+2+7x+7-8=2x^2+11x+1$.
The question is simply to evaluate the function in regards to F(x) being f(x+1) or f(-x) or even f(-5) and inputting it in the formula f(x)=2x^2+7x-8

6. ## Re: Evaluating a function

Originally Posted by M670
The question is simply to evaluate the function in regards to F(x) being f(x+1) or f(-x) or even f(-5) and inputting it in the formula f(x)=2x^2+7x-8
That does not change what I posted.

7. ## Re: Evaluating a function

Originally Posted by Plato
That does not change what I posted.

8. ## Re: Evaluating a function

Originally Posted by M670
If $f(x)=2x^2+7x-8$ then
$f(x+1)=2(x+1)^2+7(x+1)-8=2x^2+4x+2+7x+7-8=2x^2+11x+1$.
I think you mean that you are given that $f(x)= 2x^2+ 7x- 8$ and you are asked to evaluate f(x+ 1) and f(-x) though that is not at all what you are saying in your initial post or post #5.
$f(x+1)= 2(x+1)^2+ 7(x+1)- 8$ and $f(-x)= 2(-x)^2+ 7(-x)- 8$.